A novel iterative modified bicubic interpolation method enables high-contrast and high-resolution image generation for F-18 FDG-PET. Issue 52 (December 2017) - Okizaki, Atsutaka; Nakayama, Michihiro; Nakajima, Kaori; Takahashi, Koji
Abstract : Abstract: Positron emission tomography (PET) has become a useful and important technique in oncology. However, spatial resolution of PET is not high; therefore, small abnormalities can sometimes be overlooked with PET. To address this problem, we devised a novel algorithm, iterative modified bicubic interpolation method (IMBIM). IMBIM generates high resolution and -contrast image. The purpose of this study was to investigate the utility of IMBIM for clinical FDG positron emission tomography/X-ray computed tomography (PET/CT) imaging. We evaluated PET images from 1435 patients with malignant tumor and compared the contrast (uptake ratio of abnormal lesions to background) in high resolution image with the standard bicubic interpolation method (SBIM) and IMBIM. In addition to the contrast analysis, 340 out of 1435 patients were selected for visual evaluation by nuclear medicine physicians to investigate lesion detectability. Abnormal uptakes on the images were categorized as either absolutely abnormal or equivocal finding. The average of contrast with IMBIM was significantly higher than that with SBIM ( P  < .001). The improvements were prominent with large matrix sizes and small lesions. SBIM images showed abnormalities in 198 of 340 lesions (58.2%), while IMBIM indicated abnormalities in 312 (91.8%). There was statistically significant improvement in lesion detectability with IMBIM ( P  < .001). In conclusion, IMBIM generates high-resolution images with improved contrast and, therefore, may facilitate more accurate diagnoses in clinical practice.